Lukova jama v dolini Kolpe, v Sloveniji - Turk, Ivan (Arheološki vestnik, 1996)
Lukova Cave is a new Eneolithic site which also contains Pleistocene fauna (the most important being cave lion remains) in southern Slovenia.
Keywords: animal remains; archaeology; arheologija; bakrena doba; cave archaeology; cave lion; Copper Age; jamska arheologija; jamski lev; lončenina; Lukova jama; palaeontology; paleontologija; paleontology; plant remains; pottery; rastlinski ostanki; Slovenia; Slovenija; živalski ostanki